Concussion Education in Children and Youth: A Scoping Review - Scott Ramsay BSN, RN; Susan Dahinten PhD, RN, MBA (SAGE Publishing, 2020)
Introduction Sports-related concussions in children and youth are a significant health concern. There is increasing literature pertaining to levels of knowledge about concussion and the effects of educational interventions, but the literature has not yet been synthesized for the subpopulation of children and youth. Therefore, the purpose of this review was to identify and summarize the current state of the literature on concussion knowledge, and the effect of concussion education on the knowledge, attitudes, and behaviors of children and youth who engage in sports. Methods A scoping review was conducted, guided by Joanna Briggs Institute methodology. Two databases, MEDLINE and CINAHL (Cumulative Index to Nursing and Allied Health Literature), and reference lists were searched to identify relevant studies that focused on children and youth less than 19 years of age who engage in sports. We also searched Google Scholar for gray literature. Results Of the 21 articles that met inclusion criteria, 15 focused on levels of concussion knowledge, and 6 examined the effects of educational interventions. Children and youths' level of knowledge and exposure to prior concussion education varied, although more of the studies found a lack of concussion knowledge. Educational interventions of various types have been associated with short-term increases in knowledge and intention to report, but few of the studies found sustained effects. Conclusions Findings highlight the need for improved concussion education for children and youth engaged in sports. Findings also indicate a need for further research using more rigorous methods, and studies that examine subgroup differences in knowledge and factors that may moderate the effects of educational interventions.